Impacts on human and environmental health generated by the construction of multifamily buildings in the city of Lima - Suárez Salinas, Jesús (2022)
The construction of multifamily buildings stands out as one of the main economic activities in the city of Lima, it has even been considered in the first stage of economic reactivation amid the COVID-19 pandemic and to date it has managed to reach the expected expectations, however, there are significant impacts resulting from this activity that generate damage to the environment and human health. This research is descriptive, comparative, and applied; A qualitative-quantitative approach is developed through the analysis of the modified Leopold matrix that allows reaching the objective of identifying the activities of the construction process that generate the greatest environmental impacts and human health, these being: demolition, excavation and hull structure (Chávez Vargas, 2014), with the purpose of proposing mitigation and control actions. The results obtained determined that the demolition, excavation, and hull structure stages are the ones that generate the most significant negative impacts on the environment, mainly air pollution from particulate matter, gases, and environmental noise, as well as soil pollution from solid waste generation. Regarding the significant negative impacts on human health, in addition to the three stages mentioned above, it was found that damage is also generated during finishing, which can result in occupational diseases.